Pemanfaatan Bottom Ash Sebagai Bahan Substitusi Agregat Halus Terhadap Kekuatan Beton - Agnes Claudia Posedung; Frans Phengkarsa; Desi Sandy (Paulus Civil Engineering Journal, 2020)
Bottom ash is the result of coal combustion which can be useful for the use of concrete mix constituents. In this study, bottom ash is used as a substitute for fine aggregate in the manufacture of concrete. Bottom ash has a larger and heavier grain size with a characteristic dark gray color. The purpose of this study was to determine the strength of concrete using bottom ash as a substitute for fine aggregate. The percentage of the use of bottom ash as a substitute for fine aggregate is 0%, 25%, and 35%. The research was conducted at the Laboratory of Material Technology, Paulus University of Indonesia Christianity. The test objects used were 36 cylinders with a diameter of 15 cm and a height of 30 cm. Tests conducted in the form of compressive strength test, split tensile strength test, and modulus of elasticity test with a concrete quality plan of 30 MPa. From the research results, for the compressive strength test results obtained the optimum bottom ash variation at the use of 35% bottom ash with a compressive strength of 33,764 MPa at the age of 28 days, the split tensile strength test obtained the optimum variety of bottom ash at the use of bottom ash 35% with split tensile strength. of 3,253 MPa at the age of 28 days while the highest modulus of elasticity was obtained at the addition of 35% bottom ash which was 27332.0255 Mpa. And the percentage of split tensile strength relationship for bottom ash variation is 0%, 25%, and 35% of 8.007%, 8.983%, and 9.635% of the compressive strength, respectively. This value meets or is by following per under with what is determined, namely the average ranges from 7% to 11% of the compressive strength with an average of around 9%. From the variation of bottom ash, namely 0%, 25%, and 35% in cylindrical specimens, which reaches f'c 30 Mpa is bottom ash with a variation of 35% and can be used as a substitute for fine aggregate.